Group IQ Scores as Predictors of Success in Secondary Schools: A Re-evaluation - Bauman, Edward (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to re-evaluate the use of group IQ scores as predictors of academic grades and high-school completion in the light of recent changes in high-school curriculum content. A 10 percent random sample of students entering Grade 9 in Thunder Bay, Ontario, high schools in 1962 was studied. Mean IQ's are reported for students in the 4- and 5-year programs. Correlations between IQ and marks earned in each of 13 high school subjects were computed and cor- relations between grade averages and IQ. The proportion of students completing each grade was computed for each of several IQ levels. The correlations between IQ and grades in vocational courses were lower than the correlations between IQ and academic course grades. It is suggested that a minimum IQ of 80 is required for the vocational 4-year program while a minimum of 100 is needed for the 5-year academic program. If students have at least the minimum ability, then factors other t